MECHANICAL BEHAVIOR ANALYSIS OF FRUIT PONDOH DRUGS DURING THE METHOD WITH LIQTENSTEIGER MODEL PUMP - Putu Sud ira (Jurnal Penelitian Saintek, 2002)
This study  was  aimed  to  analyze  mechanical properties  of  SalakPondoh fruit  on  maturity periods  through non-linear  viscoelastics model from Lichtensteiger. Using a pneumatics impactor provided bypiezoelectric force sensor BK 8200 and acceleration sensor BK 4374, the  histories  of  the  impact forces   and  impact  acceleration  were recorded on microcomputer system. Thirty-three Salak Pondoh fruit with seven maturity levels were evaluated through impact impulse on one side.  The deformation velocity and deformation level of Salak Pondoh fruit,  due to impact were analyzed and differentiated from impact acceleration data. Using non-linear visco-elastical Lichtensteiger model, the mechanical properties of Salak Pondohfruit were analyzed quantitatively.   The result of this study shows impact force,  deformation, and deformation velocity histories were able to describefirmness and softness mechanical properties of Salak Pondoh quantitatively.